Oral Health Status and Oral Hygiene Practices among Children Having Parents with Different Levels of Dental Anxiety - Shilpa Warhekar; Ashish Warhekar; Vandana Pandey Tripathi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background : The aim of this study was to identify parents with dental anxiety using Modified Dental Anxiety Scale and comparing different levels of dental anxiety with oral health status, oral hygiene practices and treatment needs of their children.Methods: This cross sectional study included 442 children and their parents. Informed consent form and structured proforma was handed over to children explaining the purpose of study. A structured proforma includes demographic data, oral hygiene practices, Dentition status & treatment need (WHO, 1997) of children. The study subjects were also provided with self-administered MDAS questionnaire to be filled by the parents consisting of 5 items to assess parental dental anxiety.Conclusion: Compared to children belonging to anxious parents, Children of non-anxious parents had less chances of having dental caries (Adjusted Odds ratio (OR) = 0.58, 95% CI: 0.336-1.010). More than 98% of study subjects were using toothbrush and toothpaste to brush their teeth once a day in horizontal scrubbing method. The caries experience among the study population was considerably less. The reason may be that the present study was conducted on school children and some school may be in the endemic fluoride region.